Juridical Fundamentals for the Establishment of Islamic Banking Law in Indonesia - Navisa, Fitria Dewi (University of Darusssalam Gontor, 2023)
••• English ••• The existence of Islamic banks is a sign of the revival of the Islamic economy in Indonesia, especially since Indonesia is a country where the majority of its people are Muslims. So, the existence of Islamic banking in Indonesia should become an important matter because it is related to the establishment of the people's economy, moreover, Indonesia is a legal state that binds all activities and rules in legal writings that are ratified and agreed upon. This research was conducted to answer about the importance of the legal foundations of the establishment of Islamic banking law in Indonesia. This research method use a normative juridical approach. Legal research with this approach is oriented toward the norms contained in the legislation. The results is, the formal position of Islamic banking law in Indonesia is said to be strong from a juridical point of view, even in line with the position of other conventional banking. On this basis, the existence of laws and regulations related to Islamic banking in Indonesia is something that needs to exist. Because Islamic banking is the foundation of the economic milestone for the Muslim community. The existence of these laws and regulations will further strengthen the existence of Islamic banks in Indonesia, to provide services to all people with a sharia system and pattern, which is based on the Al-Qur'an and also the Hadith of the Prophet Muhammad Saw. ••• Indonesian ••• Keberadaan bank syariah merupakan tanda bagi kebangkitan ekonomi syariah di Indonesia, apalagi Indonesia merupakan negara yang mayoritas penduduknya beragama Islam. Maka keberadaan perbankan syariah di Indonesia seharusnya menjadi suatu hal yang penting karena berkaitan dengan terwujudnya ekonomi kerakyatan, apalagi Indonesia adalah negara hukum yang mengikat segala kegiatan dan aturan dalam suatu tulisan hukum yang disahkan dan disepakati. Penelitian ini dilakukan untuk menjawab tentang pentingnya landasan hukum berdirinya hukum perbankan syariah di Indonesia. Metode penelitian ini menggunakan pendekatan yuridis normatif. Penelitian hukum dengan pendekatan ini berorientasi pada norma-norma yang terkandung dalam peraturan perundang-undangan. Hasilnya, posisi formal hukum perbankan syariah di Indonesia dikatakan kuat secara yuridis, bahkan sejalan dengan posisi perbankan konvensional lainnya. Atas dasar tersebut, keberadaan peraturan perundang-undangan terkait perbankan syariah di Indonesia merupakan sesuatu yang perlu ada. Karena perbankan syariah merupakan tumpuan tonggak ekonomi bagi masyarakat muslim. Adanya peraturan perundang-undangan tersebut akan semakin memperkokoh eksistensi bank syariah di Indonesia, untuk memberikan pelayanan kepada seluruh masyarakat dengan sistem dan pola syariah, yang berlandaskan pada Al-Qur'an dan juga Hadith Nabi Muhammad Saw.